Laser Cut passing‐through Open‐to‐CHS Beam‐to‐Column Connections. Issue 2 (1st September 2021) - Das, Rajarshi; Kanyilmaz, Alper; Degee, Herve
Abstract: Although Circular Hollow Sections (CHS) have always demonstrated their excellent properties in resisting high compression, tension as well as bending in all directions, thanks to their inherent shape and geometry, the existing open ‐to‐CHS connections used in the current industry (conventional connections) generally require a substantial amount of stiffeners or gusset plates due to their construction method i.e. direct welding or diaphragm connections. As a result, huge welding quantities are required which further complicates the fabrication procedure. Furthermore, due to a direct connection, the CHS column becomes prone to localized distortions. In order to minimize the aforementioned drawbacks, a "passing‐through" approach was proposed and investigated in the EU‐RFCS research project LASTEICON where connecting elements (i.e. one or more steel plates or a piece of I‐profile) pass through the CHS column through Laser Cut slots made in the column and the primary beams (namely the "main" I‐beams) are connected to both ends of the passing through elements (named as "through‐members"). The applied shear force, and if relevant the applied moment, is effectively transferred by the "through‐member" to the CHS column, whereas, the CHS column contributes significantly in resisting it through its large flexural and shear capacity. The present article summarizes the most interesting results obtained based on the experimentally validated numerical simulations for the different types of LASTEICON connections. Thanks to the superior fabrication quality and versatility offered by the laser cutting technology, different types of connection configurations were developed within the project. This article introduces a few of these possibilities: (1) Two‐way steel moment resisting connections, (2) Asymmetric steel connections, (3) Four‐way steel connections, and (4) Composite connections.